Pemanfaatan WhatsApp Grup sebagai Media Komunikasi Gerakan Subuh Berjemaah - Azizah Nurul Islami (STIKes Ibnu Sina Ajibarang, 2024)
This research describes the use of WhatsApp Groups as a communication medium in the congregational dawn movement in Rokan Hiir. The research method uses a qualitative descriptive research type. The research results show that the WhatsApp Group GERAKAN SHUBUH BERJAMAAH is not in accordance with the initial plans for this group. This group only briefly discusses the congregation's dawn movement, discussing more about other things according to the character of the group members. However, the majority of group members did not mind it. However, there were several group members who were not happy and took the stance of leaving the group. The lack of discussion regarding the congregational dawn movement opens up opportunities for further research in the form of optimizing the use of WhatsApp Groups in the congregational dawn movement.